The problem of Fronts in the Indian Atmosphere (MAUSAM, 1966)
The present paper contains the results of a detailed synoptic investigation of a western disturbance in the typical winter month of January .This disturbance moved across West Pakistan and northern India and was prima facie associated with fronts. The investigation hs8, however, shown that there were no well-organised sloping surfaces in association with the western disturbance. The slopes were found to be very variable and did not extend above 3. O km. The potential pseudo-wet bulb temperature curves did not also show any significant air mass contrasts in the vertical, during the movement of the discontinuity surfaces across the stations. The times of commencement and cessation of precipitation had no relationship to the time at which the discontinuity at sea level moved across the synoptic stations. On the basis of these observational facts, the conclusion is drawn that, even in mid-winter, when there is a maximum probability of formation of fronts in the Indian atmosphere, discontinuity surfaces which may form due to juxtaposition of different air masses, probably get disorganised on most occasions leaving merely a broad "indeterminate" type of partition which moves with the western disturbance and causes temperature and other associated changes. The available evidence also suggests that such partitions are of little consequence in the development of hydrometeors and, therefore, would be of little value in forecasting the hydrometeors.